OHP-009 How hospital pharmacists can promote proper use of breath tests beyond buying medical devices?. (14th February 2016) - Mikolajczak, AL; Bellon, B; Calmels, V; Cestac, P; Cool, C; Duhalde, V
Abstract : Background: Carbohydrate malabsorption and small intestinal bacterial overgrowth (SIBO) cause digestive symptoms that can affect the patient's quality of life. The hydrogen breath test is the most widely used diagnostic method. Anaerobic bacteria colonising the large intestine, or the small intestine in pathological situations, produce hydrogen by fermentation of non-absorbed carbohydrates which can be measured in the breath. The lack of standardisation of measurement and interpretation of this test can lead to misclassification. Purpose: In comparison with the literature, we assessed breath test procedures used in our establishment to improve practices. Material and methods: We made an inventory of breath test practices in our gastroenterology department and compared them with the literature data 1 2 and recommendations made by manufacturers (good practice). Results: To avoid misdiagnosis, many rules have to be respected the day before: no slow sugar, no dairy products, no dietary fibre, and no medicines that can modify intestinal transit or increase hydrogen. They are not known in our department. After fasting for 14 h, patients must exhale via the device (basal value). The amount of hydrogen is measured at 30 min intervals for at least 2 h further to ingestion of sugar, which should be under 10 ppm. Over 20 ppm of hydrogen, intolerance to the tested sugar is displayed. This quantitative analysis has to be paired with a CO2 measurement: its stable value controls the breathing out quality. Some people do not produce hydrogen, but methane, owing to particular bacteria species. This quantification avoids underdiagnosis in detection of 'non-H2 producers'. Our device does not include these two options because of non-specific electrochemical cells. Our device is outdated and consumables employed are inappropriate and reused, generating an obvious lack of hygiene and incorrect calibration. Conclusion: We produced a protocol for physicians with lifestyle advice, which must be respected before examination, and measurement rules, to improve the quality of breath tests. Following multidisciplinary decisions, breath test analysis of hydrogen and CO2 will be relocated to the biology department, to standardise measurement, calibration, maintenance, interpretation (diagnosis precision) and to open accessibility to town doctors (diagnosis development). References and/or Acknowledgements: Eisenmann. J Breath Res December 2008 Ghoshal. J Neurogastroenterol Motility July 2011 No conflict of interest.